Scurvy in a young man: a rare case report - Lu, Rui-Ling; Guo, Jie-Wen; Sun, Bao-dong; Chen, Yu-Lan; Liu, Dong-Zhou (Frontiers in Nutrition, 2023)
Scurvy, resulting from vitamin C deficiency, has nonspecific constitutional symptoms, including weakness, malaise, and fatigue. It is frequently misdiagnosed due to the lack of specific clinical manifestations. Although there are sporadic cases of scurvy currently reported in children, scurvy in young people is seldom encountered. Here, we report on a 25-year-old male patient without any underlying conditions who presented with severe pain and ecchymoses of both lower extremities. He was diagnosed with scurvy due to a long history of staying indoors and inadequate intake of fruits or vegetables.